THE EFFECT OF PROBLEM-BASED LEARNING MODEL (PBL) ASSISTED BY VISUAL MEDIA APPLICATION CANVA ON THE LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS IPAS - Sabrina Yulian Nabila; Wahyu Susiloningsih; Rarasaning Satyaningsih (Media Inovasi Pendidikan dan Publikasi, 2024)
Finding the problem-based learning (PBL) learning strategy with the use of a visual media tool is the primary goal of the written research. Canva has an impact on primary school kids' science learning outcomes. because science and related subjects continue to have low learning outcomes for elementary school students. According to research that has been published in a number of journals, social studies pupils in elementary schools have not yet attained 75 KKM (Minimum Competency Criteria). To solve this issue, the visual media tool Canva was utilized in conjunction with the learning methodology known as Problem-Based Learning (PBL). With this approach, students are motivated to solve issues, collaborate with others, work actively, and apply what they have learned. They also have the chance to learn, apply what they have learned, and overcome obstacles in groups. The written research uses the visual media application Canva to make sure that the learning model, Problem Based Learning (PBL), has an impact on elementary school students' scientific learning results. Examining the study, it was found that posttest research design was combined with quantitative research methods. The study population comprised all fourth-grade pupils of SDN Sedati Gede II. Twenty-five pupils from class IV-A were selected to serve as the experimental group, and the remaining twenty-five students from class IV-C served as the control group. A multiple-choice test consisting of twenty questions and a teacher activity observation sheet were used as the data gathering tools. The T-test, the homogeneity test, and the normalcy test were the three techniques employed for data analysis. The study's findings, which were analyzed using SPSS 25, indicated that the T-test results with H0 rejected, indicating that the Problem Based Learning (PBL) learning model supported by the visual media of the Canva application had an impact on the science and natural science learning outcomes of elementary school students.